The Role of Religious Teachers in Increasing the Motivation of Students in Grade VII Catholic Religious Education and Budi Pekerti Subjects at Tri Sakti-1 Medan Junior High School - Tibo, Paulinus; Ginting, Natasya Andriani (Journal of Educational Analytics, 2024)
This study aims to determine the learning motivation of seventh grade students in the subject of Catholic Religious Education (PAK) and Budi Pekerti at Tri Sakti-1 Medan Catholic Junior High School, as well as the role of PAK teachers in motivating students. In this context, PAK teachers have a crucial role in improving learning motivation by providing appropriate encouragement and motivation to students. We expect this research to enhance the quality of education and boost students' learning motivation in schools. To be role models for students, PAK teachers must act as educators who not only teach religious values but also have broad insights and strong characters. The research methods used in this study are qualitative and quantitative. We used the qualitative method to delve deeper into students' perceptions and experiences of learning motivation from PAK teachers, while the quantitative method objectively measured the level of student learning motivation. We expect the results of this study to offer recommendations to PAK teachers, aimed at enhancing students' learning motivation and fostering the development of effective learning strategies at Tri Sakti-1 Medan Catholic Junior High School. Thus, this study has important implications for improving the quality of religious education and student character through the active and inspiring role of PAK teachers.